Effect of Thermal Barrier on Thermal Protective Performance of Firefighter Garments (Journal of Fiber Bioengineering and Informatics, 2018)
For firefighter protective clothing, thermal protective performance is of primary importance. In thisregard, the effects of thermal barrier construction on the level of thermal protection were investigated.In this study, needle punched nonwovens of varying thicknesses for application as thermal barrier wereprepared from 100% meta-aramid, 100% wool, and 90% meta-aramid/10% para-aramid fibers. Theeffect of the number of layers in multilayer thermal barriers prepared from these nonwovens and theeffect of spacers on the thermal protective performance were examined. The possibility of incorporationof aerogels into the thermal barrier to enhance the protective performance was examined. The needlepunched nonwovens were padded with 5 wt% aerogels dispersion in acetone. The differences in thermalprotective performance of nonwovens were evaluated by heat transmission on exposure to flame, heattransmission on exposure to radiant heat and heat transmission on exposure to both flame and radiantheat methods. Multi layer constructions with spacers and nonwovens treated with aerogels exhibitedhigher thermal protective performance.